2021
DOI: 10.1088/1361-6587/ac1ea4
|View full text |Cite
|
Sign up to set email alerts
|

Ballooning instability preventing the H-mode access in plasmas with negative triangularity shape on the DIII–D tokamak

Abstract: Infinite toroidal mode number (n = ∞) ballooning mode analysis of negative triangularity discharges on DIII-D shows that the access to 2 nd stability becomes strongly restricted when the top triangularity decreases even modestly from −0.18 to −0.36. This is observed in experiment to coincide with the suppression of the L-H-transition. Further theoretical analysis with ballooning mode limited pedestals shows that the threshold for opening the 2 nd stability access rises from a pedestal temperature of 0.3-1 keV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
48
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 38 publications
(45 reference statements)
10
48
0
2
Order By: Relevance
“…The relationship between access to the 2 nd stability region and high pedestal H-modes has been observed experimentally on many machines, including on DIII-D [17,[25][26][27], JET [28,29], JT-60U [30], NSTX [31] and Alcator C-Mod [32]. In these cases, pressure gradients in the edge have been found to exceed the first infinite-n ballooning stability limit (calculated in the limit of high magnetic shear) by accessing the 2 nd stable region.…”
Section: Relationship Between Ballooning Stability and H-mode Accessmentioning
confidence: 87%
See 4 more Smart Citations
“…The relationship between access to the 2 nd stability region and high pedestal H-modes has been observed experimentally on many machines, including on DIII-D [17,[25][26][27], JET [28,29], JT-60U [30], NSTX [31] and Alcator C-Mod [32]. In these cases, pressure gradients in the edge have been found to exceed the first infinite-n ballooning stability limit (calculated in the limit of high magnetic shear) by accessing the 2 nd stable region.…”
Section: Relationship Between Ballooning Stability and H-mode Accessmentioning
confidence: 87%
“…When operating at δ < 0, the plasma experiences a significant bulge outwards towards the low field side, dramatically increasing the region of the plasma in the bad curvature region, which contributes significantly towards the destabilization of infinite-n ballooning modes. As such, the infinite-n stability limit has been proposed as a primary instability in the NT edge [14][15][16][17][18]. Recent experimental work on DIII-D has demonstrated that, while H-mode can be achieved at modest negative triangularity, it is quickly lost when δ is decreased below some critical value [17].…”
Section: Effects Of Shape On Infinite-n Ballooning Stabilitymentioning
confidence: 99%
See 3 more Smart Citations